Clinical Diagnosis of Achalasia: How Reliable is the Barium X-Ray? - I El-Takli; P O’Brien; WG Paterson (Canadian Journal of Gastroenterology)
Manometry is considered to be the gold standard for the diagnosis of achalasia. However, many physicians believe that contrast radiography, classically showing esophageal dilation with bird-beak narrowing of the gastroesophageal junction, is also accurate in either diagnosing or excluding the disorder. The aim of the current study was to determine the accuracy of barium x-ray in the diagnosis of achalasia. The radiological diagnosis of all patients manometrically diagnosed with achalasia (using conventional criteria) between January 1994 and June 1998 were reviewed. A total of 51 cases of achalasia were identified. Thirteen patients were excluded because they either did not have contrast radiography before a manometric diagnosis or had their x-rays performed more than six months previously. Of the remaining 38 patients, achalasia was stated as a diagnostic possibility in the radiologists report in only 22 (58%) of those patients. Achalasia was not considered in the remaining 16 patients: two were reported as normal, four as having stenosis/narrowing in distal esophagus, two as having presbyesophagus, one as having mild gastroesophageal reflux and seven as having nonspecific dysmotility. To determine the reason for the diagnostic failure of the barium x-ray, an expert gastrointestinal radiologist reviewed 12 of the nondiagnostic x-rays in a blinded fashion, interspersed with 10 randomly selected esophageal-contrast radiographs from control subjects to avoid bias. Of these initially nondiagnostic x-rays in achalasia patients, typical radiological features of achalasia were deemed to be present in 50%. The present study indicates that contrast radiography lacks sensitivity in the diagnosis of achalasia. This is not only due to radiologist oversight but also because of the absence of the characteristic radiological features in many cases. This reinforces the important role of esophageal manometry in patients with persistent nonstructural dysphagia.